2021
DOI: 10.3390/toxins14010018
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Adverse Events in Bee Venom Therapy Reported in South Korea: A Survey Study

Abstract: This study was aimed at investigating Korean patients’ experience with bee venom therapy (BVT) and providing evidence to enhance BVT safety. Thus, an anonymous online survey was conducted between August 22 and 28, 2018. Five hundred respondents who underwent pharmacopuncture (PA) within one year were surveyed (sample error: 95 ± 4.38%). Of these, 32 respondents were excluded and 468 were evaluated. Of the 468, 61 reported experiencing adverse events after PA. The adverse event rate was higher in the BV-PA(Bee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…However, there were case reports of two deaths due to anaphylaxis after BVA treatment [17]. Clinical use of bee venom is limited owing to these severe cases of adverse effects; however, there is no clear evidence leading to the conclusion that bee venom therapy (BVT) is not safe [18]. In fact, two large cohort studies included in our review suggested that the incidence rate of anaphylaxis in response to BVA is 0.034% and 0.019% in 32,000 and 15,783 patients, respectively [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…However, there were case reports of two deaths due to anaphylaxis after BVA treatment [17]. Clinical use of bee venom is limited owing to these severe cases of adverse effects; however, there is no clear evidence leading to the conclusion that bee venom therapy (BVT) is not safe [18]. In fact, two large cohort studies included in our review suggested that the incidence rate of anaphylaxis in response to BVA is 0.034% and 0.019% in 32,000 and 15,783 patients, respectively [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…In traditional East Asian medicine, BVP is used for the treatment of various diseases. Studies on the incidence of AEs and relevant factors are continuously published to prevent and identify AEs that can occur when performing BVP [ 6 , 7 , 8 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bee venom has promising anti-inflammatory and immunomodulatory characteristics. [ 17 ] Therefore, it is widely used to control inflammation and alleviate musculoskeletal pain in Asia, Eastern Europe, and South America. [ 17 ] Several clinical trials have been conducted to evaluate the effectiveness of bee venom for managing lower back pain and have demonstrated its positive therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] Therefore, it is widely used to control inflammation and alleviate musculoskeletal pain in Asia, Eastern Europe, and South America. [ 17 ] Several clinical trials have been conducted to evaluate the effectiveness of bee venom for managing lower back pain and have demonstrated its positive therapeutic effect. [ 8 , 9 , 18 ] As bee venom has a strong toxic effect, only a minimal dose of diluted bee venom is allowed in clinical practice.…”
Section: Discussionmentioning
confidence: 99%